The probability in the problems of high school Math Olympics in Spain - José Miguel Rubio-Chueca; José M. Muñoz-Escolano; Pablo Beltrán-Pellicer (Universidad de La Rioja, 2021)
Among the participants in Mathematical Olympiads, it is usual to find mathematically gifted students. Therefore, from the point of view of the research about gifted students, it is interesting to analyze the problems proposed in these events. The objective of this work is to analyze the cognitive demand, the languages and the procedures of the mathematical tasks proposed in the problems on probability in the individual tests of both the semifinal and the final in the Aragonese Mathematical Olympiad (1989-2019) and the problems carried out in the individual test of the National Mathematical Olympiad (1990-2019). We focus our attention on probability problems to characterize the representativeness of this content in the Olympics. The results show that all the proposed tasks in the Olympics are of a high level according to the cognitive demand model, which is suitable as a proposal for the high mathematical ability students, including tasks of the higher level according to the same model, whose satisfactory resolution could become an indicator of high mathematical ability. On the other hand, the scarcity of probability problems in these tests, shows the need to propose more in these contests, promoting their learning in secondary education.